Matrix metalloproteinase-2 gene polymorphisms are associated with ischemic stroke in a Hainan population. Issue 39 (September 2018) - Niu, Fanglin; Wei, Boping; Yan, Mengdan; Li, Jing; Ouyang, Yongri; Jin, Tianbo
Abstract : Abstract: Ischemic stroke is a complex vascular disease, which has become 1 of the major causes of morbidity and mortality worldwide. More and more data showed that matrix metalloproteinases (MMPs), in particular, MMP-2 are deleterious after ischaemic stroke. This study investigated the relationship between MMP-2 and stroke risk in the Southern Chinese population. We evaluated single nucleotide polymorphisms (SNP) of MMP-2 in stroke patients in an association study using a case-control design. Six SNPs of MMP2 were selected and genotyped by Agena MassARRAY. SNPStats, Haploview was used to analyze genetic data. Two SNPs in the MMP-2 gene were significantly associated with stroke risk. For rs1132896 (C versus G allele), the C allele was significantly reduced stroke risk (OR = 0.56, 95% confidence intervals [95% CI] = 0.39–0.81, P = .002). The effect of the T allele of rs243849 was IS risk according to an additive genetic model (OR = 0.67, 95% CI = 0.47–0.96, P = .028). We did not found any strong linkage between the six SNPs (rs1132896, rs1053605, rs243849, rs243847, rs243832, rs7201) The results presented strongly indicate that MMP-2 genetic variants are an important mediator of stroke risk.